Examining the Role of Deepfake Technology in Organized Fraud: Legal, Security, and Governance Challenges - Lin, Leo S.F. (Frontiers in Law, 2025)
Deepfake technology has evolved astonishingly by applying artificial intelligence (AI) to inspire ultra-realistic audio and video content. Initially praised for its legitimate use cases in entertainment and education, deepfake technology has increasingly become a tool for organized fraud and other malicious purposes. This paper investigates the role of deepfake technology in enabling identity theft, financial fraud, and unlawful activities. By conducting a qualitative comparative analysis of three cases, this paper analyzes deepfakes' legal, security, and governance aspects, indicating that deepfakes have posed a massive threat at the national and global levels. Also, this research demonstrates how the current regulatory regimes cannot adequately mitigate these emerging threats. The results expose glaring deficiencies in accountability and enforcement, which are made even more glaring by the global character of the internet and the accelerative pace of technological innovation. This research provides implications of deepfake technology in organized fraud and offers policy recommendations to mitigate the threats and prevent misuse of deepfake technology in the future.